Determinants of the Level of Islamic Bank Compliance with Mudharabah Principles: Evidence from Indonesia - Hakim, Luqman; Sulhani, Sulhani (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
This study aims to examine the determinants of Islamic banks compliance with the Statement of Financial Accounting Standards (SFAS) No.105 on Mudharabah principles. The sample, selected using purposive sampling, was 96 observed data of Islamic Banks (IBs) in Indonesia between 2009 and 2017. The data were analyzed using panel data regression. Using the multiple regression analysis techniques, this study demonstrated a significant positive influence of the effectiveness of the Shariah Supervisory Board (SSB), the effectiveness of audit committees, tenure of CFO, and third party funds from the Mudharabah contract for the compliance level of the IBs financial reports with SFAS No.105. Meanwhile, the CFO educational background had a significant negative effect and institutional ownership did not have any significant effect on the compliance level. Thus, to attain a higher level of compliance with SFAS 105, the Indonesian IBs must improve the quality of the reporting system monitor through the effectiveness of SSB and the audit committees